2012
DOI: 10.1109/tgrs.2011.2175737
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Motion Error Estimation Method Based on Raw Data

Abstract: High-resolution airborne synthetic aperture radar (SAR) systems are very sensible to deviations of the aircraft from the reference track. In high-resolution imagery, the improvement of range resolution increases the difficulty of implementing range cell migration correction (RCMC), while a wider synthetic aperture increases the cumulative time of motion errors which will affect the image quality. To enable accurate motion compensation in image processing, a high-precision navigation system is needed. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…The residual motion errors estimation methods from individual imagery can also help to improve the focusing quality in the azimuth, when the estimated residual errors are applying back to the imaging processing. Many studies have been reported on the airborne SAR motion compensation (Fornaro 1999;Fornaro, Franceschetti, and Perna 2005;Li et al 2013;Prats, Reigber, and Mallorqui 2005;Li et al 2012). Howerver, few literatures just focuse on the residual motion errors estimation from the individual SAR imagery.…”
Section: Overview the Methods For Rsidual Motion Errors And Time Varymentioning
confidence: 99%
“…The residual motion errors estimation methods from individual imagery can also help to improve the focusing quality in the azimuth, when the estimated residual errors are applying back to the imaging processing. Many studies have been reported on the airborne SAR motion compensation (Fornaro 1999;Fornaro, Franceschetti, and Perna 2005;Li et al 2013;Prats, Reigber, and Mallorqui 2005;Li et al 2012). Howerver, few literatures just focuse on the residual motion errors estimation from the individual SAR imagery.…”
Section: Overview the Methods For Rsidual Motion Errors And Time Varymentioning
confidence: 99%
“…In practice, the normalization factor is the average of data within the center part of one line. The traditional method to compute the normalization factor is expressed as formula (1).…”
Section: The Traditional Methods For Image Intensity Adjustment On Azimentioning
confidence: 99%
“…But the unsteadiness is the generally shortcoming of these low altitude platforms [1]~ [7]. The unsteadiness of the low altitude platforms leads to the instability of the antenna beam center.…”
Section: Introductionmentioning
confidence: 99%
“…However, one of the problems is that the data rate of INU or GPS is usually much lower than the azimuth sampling frequency, while the interpolation may bring about extra errors and reduce the precision. The other commonly used way to obtain the motion error is to estimate the trajectory deviation directly from the raw data [7][8][9][10][11][12][13][14][15][16][17]. It is based on the concept that the uniformly azimuth-sampled data without motion errors has its intrinsic coherence, while the motion error is random.…”
Section: Introductionmentioning
confidence: 99%